Improvement of the Regulation of Tourism Activities in Modern Conditions - Potekhina, Elena; Putrik, Yurii; Barsukov, Sergey; Smirnova, Anastasiya; Tretyak, Elena (Anais Brasileiros de Estudos Turísticos, 2022)
The aim of the study lies in improving approaches to the regulation of tourism activities in modern conditions. We consider that the orientations of the regulation of the development of tourism activities are represented by the normative and legal, economic, social and information spheres. The study analyzes and identifies the favorable conditions for each sphere, evidencing that: (a) in the normative and legal spheres, conditions should be created for the development of public-private partnerships through the design of strategies for the development of tourism clusters and the use of the instruments of tax investment loans for tourism enterprises; (b) in the economic sphere it is necessary to develop effective organizational and economic support measures for the promotion of the brand of the Russian Federation on international markets for tourism services; c) in the social sphere it is necessary to develop social tourism, in particular, family, children, business and green tourism, moreover, it is noted, d) in the information sphere, the desirability of developing cooperation with institutions of higher education and support and public recognition of the status of the subjects of tourism activity.